Respuesta :

Answer:

SHOWN BELOW!!!!

Step-by-step explanation:

KEEP IN MIND ----> *Square root of a number is a value, which on multiplication by itself gives the original number. The square root is an inverse method of squaring a number.*

Alright so the first equation C^2 - 49 = 0

Step 1 : Add 49 to both sides

C^2 - 49 + 49 = 0 + 49

C^2 = 49

Step 2 : Take the square root

(squ root) C^2 = (squ root)49

C = +/- (squ root) 49

Final answer ---> C = 7 OR C = -7

2.) 4S^2 - 100 = 0

Step 1 : Add 100 to both sides

4S^2 - 100 + 100 = 0 + 100

4S^2 = 100

Step 2 : Divide both sides by 4

4S^2/4    =   100/4

S^2 = 25

Step 3 : Take the square root

(squ root) S^2 = (squ root) 25

S =  +/- (squ root) 25

Final answer ---> S = 5 OR S = -5

3.) 9x^2 = 324

Step 1: Divide both sides by 9.

9x^2/9 = 324/9

x^2 = 36

Step 2: Take the square root

squ root) x^2 = (squ root) 36

x = +/- (squ root) 36

Final answer ---> x = 6 OR x = -6

ACCESS MORE